2015
DOI: 10.1111/jcmm.12496
|View full text |Cite
|
Sign up to set email alerts
|

Advanced research on vasculogenic mimicry in cancer

Abstract: Vasculogenic mimicry (VM) is a brand-new tumour vascular paradigm independent of angiogenesis that describes the specific capacity of aggressive cancer cells to form vessel-like networks that provide adequate blood supply for tumour growth. A variety of molecule mechanisms and signal pathways participate in VM induction. Additionally, cancer stem cell and epithelial-mesenchymal transitions are also shown to be implicated in VM formation. As a unique perfusion way, VM is associated with tumour invasion, metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
235
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(243 citation statements)
references
References 148 publications
6
235
0
2
Order By: Relevance
“…[22][23][24] FACS analysis to assess the proportion of CD44 þ /CD24 À CSCs revealed that greater than 90% (94.3% AE 1.8) of the MDA-MB-231 cell population was composed of CSCs; this high proportion of CSCs is a characteristic of basal cell lines. The observation that the majority of cells in the MDA-MB-231 cell line have stem-like properties was in agreement with previous reports.…”
Section: Mda-mb-231 Cells Have a High Proportion Of Cancer Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24] FACS analysis to assess the proportion of CD44 þ /CD24 À CSCs revealed that greater than 90% (94.3% AE 1.8) of the MDA-MB-231 cell population was composed of CSCs; this high proportion of CSCs is a characteristic of basal cell lines. The observation that the majority of cells in the MDA-MB-231 cell line have stem-like properties was in agreement with previous reports.…”
Section: Mda-mb-231 Cells Have a High Proportion Of Cancer Stem Cellsmentioning
confidence: 99%
“…24 Lin et al reported that transgelin downregulation resulted in a reduction in the expression of some EMT markers such as vimentin and fibronectin-1. 13,15,48 Thus, one of the possible mechanisms through which transgelin affects VM is via EMT.…”
Section: Blocking Cxcr2 Receptor Signaling Impairs Proliferation and mentioning
confidence: 99%
See 1 more Smart Citation
“…The growth and spread of tumors depends on the formation of an adequate vascular support and amoeboid mode of tumor cell invasion (9). Furthermore, several studies have indicated that VEGF serves a role in promoting endothelial cell proliferation and migration, and induces a direct effect on cell proliferation and invasiveness (3,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…To further increase the therapeutic effect in HCC, miR195, a powerful gene drug inhibiting VEGF, and fasudil, a serine/threonine protein kinase blocking Rho kinase, were simultaneously encapsulated in the same nanoparticles (NPs) in order to suppress VM. [10][11][12][13] The cellular membrane plays the role of a selectively permeable barrier, which also presents a major barrier for intracellular delivery of cargo like plasmid DNA (pDNA), miRNA, small interfering RNA, and drugs. Although the small noncoding RNAs have been extensively studied as novel therapeutics for cancer treatment, large molecular weight, instability in blood circulation, and anionic surface charges have hindered the translation of these RNAs from bench to clinic.…”
Section: Introductionmentioning
confidence: 99%